Correlation of Breakfast with Learning Concentration in Fourth Grade Elementary School - Alice Yeni Verawati Wote; Mardince Sasingan; M. M. Puji Nitis Kusumawati (Journal of Psychology and Instruction, 2022)
The students really need nutritional intake therefore breakfast is very important for them. Children who are accustomed to breakfast will have better abilities than children who are not accustomed to breakfast. Breakfast will stimulate growth and maximize children's abilities at school. This study aims to analyze the correlation of breakfast with the learning concentration of fourth grade elementary school students. The method used in this research is a survey method by conducting treatments in data collection, by distributing questionnaires, tests, structured interviews, and so on. This study uses a descriptive approach. The subjects in this study were 24 students including 11 male students and 13 female students. While the research stages are: 1) Documentation; 2) Questionnaire (Questionnaire preparation, Questionnaire Validity Test, Questionnaire Reliability Test. The instrument or measuring instrument used is the Likert Scale and the data analysis technique used is using "significant test" the correlation test can analyze how the relationship between x and y variables. To calculate item analysis and correlation, the product moment correlation coefficient formula is used. The results of the research show that the correlation between Breakfast and Learning Concentration results in the number 0.987 where the resulting number is positive. This shows that there is a very close relationship between Breakfast and Student Learning Concentration. Based on the results of the correlation analysis, the hypothesis proposed is that there is a relationship between breakfast and student concentration. It means that there is a very significant relationship between breakfast and the learning concentration of fourth grade elementary school students.